A study of etiology and asthma risks in infants and toddlers hospitalized for recurrent or persistent wheezing - Yi, Qiuwei; Liu, Shanshan; Qiao, Jingjing; Chen, Yulan; Huang, Lu; Zheng, Yuejie; Bao, Yanmin; Shen, Kunling (Frontiers in Pediatrics, 2025)
ObjectiveTo study the etiology of recurrent and persistent wheezing in infants and toddlers, and identify the risk factors for infantile asthma.MethodsWe retrospectively analyzed the data of 612 children (aged 0–36 months) hospitalized for recurrent or persistent wheezing between 2019.09.01 and 2022.08.31. We comparatively analyzed their clinical, laboratory, imaging, and lung-examination data between different groups. Multivariate logistic regression analysis was used to identify risk factors for asthma.ResultsThe etiologies of recurrent and persistent wheezing significantly differed (P < 0.05). The top 3 causes of recurrent wheezing were viral infections (48.4%), infantile asthma (28.0%), and protracted bacterial bronchitis (PBB; 9.5%), whereas the top 3 causes of persistent wheezing were PBB (67.5%), tracheomalacia (22.2%), and infantile asthma (15.9%). The distribution of etiologies varied by age. Bronchoscopy was performed for 181 children, and mainly showed purulent changes (34.3%), tracheomalacia (27.1%), and positive pathogenic bronchoalveolar lavage fluid (25.4%). Older age, admission to the intensive care unit (ICU), positive modified Asthma Prediction Index (mAPI), and food allergy were risk factors for asthma. The odds ratio of mAPI was 4.066. The area under the receiver operating characteristic curve of the risk factors for predicting asthma was 0.8016.ConclusionWheezing phenotype and age may partly guide the etiological diagnosis of recurrent/persistent wheezing in infants and young children. Bronchoscopy is important for the diagnosis of refractory recurrent/persistent wheezing, while mAPI aids in the diagnosis of asthma. When infants and children with recurrent or persistent wheezing have the characteristics of older age, ICU admission, positive mAPI, and food allergy, the possibility of asthma may be considered.